Unique Subclavian Vascular Ring Anomaly: Insights from CT Angiography - Radu Octavian Baz; Mihaly Enyedi; Cristian Scheau; Andreea Cristiana Didilescu; Radu Andrei Baz; Cosmin Niscoveanu (Life)
Aortic arch anomalies represent a range of congenital vascular malformations resulting from disruptions in the typical embryological development of the aortic arch and its branches. These anomalies, which vary widely in their presentation, can lead to significant clinical symptoms depending on their structure and position. We report the case of a 75-year-old male with intermittent hypertension, palpitations, and episodic warmth in the upper body. Computed tomography (CT) angiography revealed an atypical aortic arch anatomy with a unique right subclavian artery anomaly. The aortic arch displayed a typical orientation but included an additional arterial branch arising from the medial wall of the descending aorta. This aberrant branch with a tortuous aspect coursed posteriorly around the esophagus and merged with the subclavian branch of the brachiocephalic trunk, forming a vascular ring. A possible embryological hypothesis requires the persistence of both the distal segment of the right dorsal aorta and the right seventh intersegmental artery, as well as the right fourth aortic arch; however, the imaging aspect of our patient is not that of a classic double aortic arch. This case emphasizes the importance of advanced imaging techniques, such as CT angiography, in identifying and managing rare vascular anomalies that may influence patient care and clinical outcomes.